Implicit attitudes in language learning - Al-Hoorie, Ali (2017)
The field of language motivation is almost 60 years old. Throughout these decades, one idea has been persistent: Motivation is assumed to be a conscious process on which the learner can exert direct control. That this conscious conceptualization might not give the full picture has not been seriously entertained. An important consequence ensuing from this approach is the overreliance on self-report measures, such as questionnaires and interviews. Thus, in effect, the individual’s conscious reflection on their own attitudes and motivation has been the primary source of empirical data for our field. This thesis challenges this hegemony of conscious motivation. It provides an extensive review of the various paradigms of unconscious attitudes and motivation. It traces back their origins, highlights some of their major findings, and reviews the instruments used within each paradigm to circumvent direct self-report (as well as the controversies surrounding these instruments). The review also demonstrates that the adoption of an unconscious perspective is not inconsistent with major theoretical frameworks in the field. It then selects one of these paradigms, namely implicit attitudes, to apply in the context of language learning. Two studies were conducted on two independent samples (with almost 700 participants in total), in two different contexts (the UK and Saudi Arabia), and with different instruments of implicit attitudes (the Implicit Association Test and the Single-Target Implicit Association Test). Study 1 found that openness to language speakers at the implicit level is associated with more openness at the explicit level. Study 2 successfully replicated this finding, and extended it to language achievement—showing that learners with more favorable attitudes toward language speakers at the implicit level achieved higher grades in their English class. This finding could not be explained away by either social desirability or cognitive confounds. The results from these two studies were also meta-analyzed using Bayes factors in order to give an overall picture of the findings. The Discussion chapter wraps up this thesis by highlighting the relevance of this unconscious approach to the field more broadly. This chapter reviews a number of recent studies that have yielded similar findings to those from the current thesis. Some of these findings are then critically reanalyzed and reinterpreted in the context of unconscious motivation, thus demonstrating how adopting an unconscious approach helps view existing findings in a new light. In some cases, the analysis casts doubt on established ideas that have been taken for granted for decades. The overall message of this thesis is not that conscious motivation should be disregarded. Instead, conscious motivation should be complemented with a consideration of the role of unconscious motivation. A conscious-only approach would offer a limited window into human attitudes and motivation.